DEVELOPMENT OF SMALL AND MEDIUM ENTERPRISES IN SERBIA FOR THE PERIOD 2015−2020. YEARS - Orlandić, Milja; Dodovska Blagoevska, Katerina; Dodovski, Aleksandar (Journal of process management and new technologies, 2023)
The sector of small, medium enterprises and entrepreneurs has an important role in economic development of all countries. In recent years, they have become carriers of economic growth, regardless these are countries with developed economies, developing countries or countries in transition. These businesses entities contribute to increasing dynamics of the economy and improving its competitiveness. Their basic role in the economic system is to solve the problem related to low economic activity, low innovation, low level of competitiveness, unequal distribution of wealth and income, as well as high unemployment rate through the creation of new jobs. In Serbia, they also represent an important economic factor of development. Given that, they have the potential for further growth and development, this paper is about analysis of the development of the entrepreneurial sector in Serbia and neighboring countries, with special reference to the period from 2015 to 2020 years. The sector of small and medium enterprises is an extremely important economic segment, as the analysis of the development of this sector will show.